1999
DOI: 10.1073/pnas.96.19.10875
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pathogenicity island, which contains genes for virulence and avirulence, on a large native plasmid in the bean pathogenPseudomonas syringaepathovar phaseolicola

Abstract: The 154-kb plasmid was cured from race 7 strain 1449B of the phytopathogen Pseudomonas syringae pv. phaseolicola (Pph). Cured strains lost virulence toward bean, causing the hypersensitive reaction in previously susceptible cultivars. Restoration of virulence was achieved by complementation with cosmid clones spanning a 30-kb region of the plasmid that contained previously identified avirulence (avr) genes avrD, avrPphC, and avrPphF. Single transposon insertions at multiple sites (including one located in avrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
253
1
24

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(282 citation statements)
references
References 59 publications
4
253
1
24
Order By: Relevance
“…2) with high similarity to XerC, a prototypical phage integrase (tyrosine recombinase). Such genes have often been found near the beginning of chromosome regions thought to result from the horizontal transfer of DNA into the current host [7,8,10]. The gene next to the 818 integrase encodes a product of unknown function (ORF 2, Fig.…”
Section: I) Gene Transfer Blockmentioning
confidence: 99%
“…2) with high similarity to XerC, a prototypical phage integrase (tyrosine recombinase). Such genes have often been found near the beginning of chromosome regions thought to result from the horizontal transfer of DNA into the current host [7,8,10]. The gene next to the 818 integrase encodes a product of unknown function (ORF 2, Fig.…”
Section: I) Gene Transfer Blockmentioning
confidence: 99%
“…Phospholipid-binding assays were carried out as described (29). To determine ␤-glucuronidase activity, plasmid pDGUS (30) carrying the E. coli uidA gene was introduced into Psph strains by triparental mating as described (27). GUS activity was quantified as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…Pathogenicity tests of Psph strains on bean (Phaseolus vulgaris L.) were performed as described (27). Hemolytic activity was assayed as described (5).…”
Section: Methodsmentioning
confidence: 99%
“…3). Indeed, at least nine effectors have been described that enable a pathogen to suppress or evade HR-based PCD 21,26,27,[90][91][92][93][94] .…”
Section: Bacterial Suppression Of Hr-based Pcdmentioning
confidence: 99%
“…The effector protein VirPphA (also known as HopAB1) was the first example of an effector that modulated HR-based resistance 92 . It was observed that a normally virulent strain of P. syringae pv.…”
Section: Bacterial Suppression Of Hr-based Pcdmentioning
confidence: 99%